The Problem of Building a Sakinah Mawaddah Warahmah PMI Family in West Java Maqashid Sharia Perspective - Ali Mutashom; Adang Djumhur Salikin; Abdul Aziz; Hajam (Lembaga Bale Literasi, 2026)
This research is motivated by the gap between the ideality of the concept of the sakinah family in Islamic Family Law and the reality of the problems faced by Indonesian Migrant Worker (PMI) families in West Java, which is manifested in the disruption of livelihood functions, communication degradation, and childcare challenges. This research aims to analyze the dynamics and problems of PMI households and formulate solutions based on Sharia Maqashid. This qualitative research with a descriptive-analytical approach combines field research and literature studies. Primary data was obtained through in-depth interviews with 22 informants (PMIs from West Java working in Hong Kong, abandoned families, and BP2MI officials), using purposive sampling techniques. Secondary data is sourced from the Qur'an, Hadith, jurisprudence, regulations, and indexed journals. The results showed that the household problems of migrant workers were an accumulation of five factors: weak religious understanding, low quality of communication, social environmental pressure, prolonged physical separation, and absence of structured assistance. The impact includes the degradation of ?if? al-d?n, ?if? al-nafs, ?if? al-nasl, and ?if? al-m?l, with ?if? al-nasl being the most critical point as migrant children lose emotional and spiritual nurturing. This study concludes the need to reconstruct a cross-phase and cross-actor approach, and formulates four models of family strengthening: distance religious coaching, community-based psychosocial assistance, transnational childcare with extended family involvement, and a deconference-based productive and fair remittance management system.